Implementasi Kode Etik Jurnalistik Pada Praktik Citizen Journalism Di Media Sosial - Pamungkas, Akbar Doni; suherdiana, Dadan; Tresnawaty, Betty (Annaba: Jurnal Ilmu Jurnalistik, 2020)
This study aims to see how the application of journalist independence, how to apply the guidelines for journalists not to write fake news and how to apply the guidelines for journalist about writing wrong news on disaster information writing by citizen journalism on instagram Jktinfo. This research uses content analysis method and qualitative approach. Data collection techniques in this research are through documentation study and literature study. Found results in the application of the journalistic code of ethics article 1 regarding the level of accuracy there are still two less accurate information, then in article 4 all information has been applied regarding not making fake news, while in the application of article 10 there are 2 inaccurate information but only one information that applies the journalistic code of ethics article 10.